Pengaruh Sanksi Pajak Terhadap Kepatuhan Pajak yang Dimediasi oleh Variabel Kesadaran Pajak - Zagoto Reaksi; Gohae Simfrosa Anskaria; Zalogo Fitilai Erasma; Hulu Faebuadodo Perlindungan (AKUNTANSI 45, 2024)
This study was conducted to analyze the effect of Tax Sanctions on Tax Compliance mediated by the Tax Awareness Variable. Data were collected from 99 respondents, namely restaurant and food stall owners in the South Nias region. The data analysis method used is path analysis. The data analysis process is carried out using SmartPLS to calculate the PLS Algorithm and then verify the hypothesis. The results of the study show that Tax Sanctions and Tax Awareness have a direct and significant effect on Tax Compliance, then the Tax Sanctions and Tax Service Quality variables also have an indirect effect on Tax Compliance through the mediation of Tax Awareness.